SUFFIXES AND PREFIXES - Gʻulomjonova Aziza Abduhalil qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. This article delves into the significance, usage, and educational impact of suffixes and prefixes in the English language. It includes an introduction to the topic, a literature review on their role in language learning, methods used in studying their effectiveness, results of the study, and a discussion of findings along with conclusions and suggestions for further research.